Usefulness of chorionic villus sampling for prenatal diagnosis of thalassaemia: a clinical study in eastern India - Dasgupta, Sujoy; Chaudhury, Kalyansree; Mukherjee, Kanchan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Aim: To review the usefulness of chorionic villus sampling for prenatal diagnosis of thalassaemia with focus on risk of miscarriage and stillbirth in Indian women and thus provide local data for counseling the prospective parents in similar situation. Methods: This retrospective study reviewed the pregnancy outcome of 362 patients with thalassaemia who underwent transabdominal chorionic villus sampling between 10-13 weeks of gestation for prenatal diagnosis. Aspiration of chorionic villus tissue was done in 2 ml normal saline under ultrasound guidance. Results: The miscarriage (pregnancy loss before 24 completed weeks) rate in our study was 2.02%. The stillbirth (pregnancy loss at or after 24 completed weeks) rate was 27 per 1000 total births. There was no incident of any limb deficiency in our study. In all cases adequate chorionic villus tissue was obtained for analysis. Conclusions: Thalassaemia is a prevalent condition in Eastern India. Chorionic villus sampling is an effective and safe method for early diagnosis of fetal thalassaemia that helps to prevent birth of thalassaemic babies.